Neo-Imperialism in Africa : Case Study Sierra Leone - Ait Ali Yahia, Radia (My University, 2020)
After the end of the era of direct colonialism in Africa, and after the independence of African lands, the ex-Europeans forces resorted to indirect methods represented in their new colonization of their former colonies in order to maintain their influence in the world, to strengthen their position and to feed their economies. European establishments during the 19th and 20th centuries played a major role in achieving their goals. This new type of domination is considered as a result of their practices during the direct colonization. They started managing the same fields that they previously used to control, but in a significant way, with a focus on the cultural aspect that works to brainwash Africans. Since the British Empire was the largest formal empire that the world had ever known, its power and influence stretched all over the globe; shaping it in all manner of ways. It has been considered as the creative of neo colonialism because it has done several works and operation that encouraged this imperialism. Commonwealth of Nations was one of neo-imperialism’s actions that enabled Britain to maintain its influence in its former colonies. In addition to the commercial and economic treaties and friendships with these countries that only serve the British and contribute to several crisis for African states. As one of the wealthiest countries of the world in terms of raw materials, where the biggest diamond has been founded, Sierra Leone is classified among the poor Third World countries that suffer from the most difficult conditions. This research focus on the reasons behind the underdevelopment of Africa and the policies used by the British and all the Western powers in Africa, with the investigation of International, economic relations and treaties between them and the effects of these new policies.
Keywords: Imperialism; Western Powers; Third World War; Former Colonies; European Expansions; British Empire; Neo-imperialism; Sierra Leone